Evaluation of Solid Waste Management in Al- Samawah City - Naser Mohammed A.; Al-Tuwayyij Husham (E3S Web of Conferences, 2023)
The purpose of this study was to look into the evaluation of waste disposal stages (collection, storing, treatment, transporting, and landfilling) in addition to additional variables, including financial status, population size, and the technical methods employed to identify relationships with the handling of waste using the Statistical Package for the Social Sciences (SPSS) software. The AL-Samawah municipality's waste management wasn't staged due to no sorting and treatment processes, and the work was limited to solid waste collection and transportation. The landfill stage was carried out in a manner that did not preserve the environment and was limited to dumping waste on the earth's surface or digging a shallow trench into which waste was placed and backfilled. It is evident through costs, as collection and transportation costs account for 95% of total waste management costs. Working families generated more waste than non-working families, ranging from 3 to 15%, due to their reliance on fast food wrapped in plastic and cork containers, which generates more waste. The regression equations were created to predict the dumping cost based on the dependent variables: transportation and collection. The R2 values were 0.77.